CHRISYE’S BIOGRAPHY WEBSITE DESIGN APPLICATIONS USING MICROSOFT FRONTPAGE 2003. - Ana Yoeni Kurniati; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Media information is a means to convey a message or information that we have received both orally and in writing, and various kinds such as newspapers, television, radio, and computers. Information plays a very important for human life. The required information must be information very quickly, accurately, and can be accounted for authenticity by many, especially among people for business, entertainment, and various other information. The Internet is a global collection of (global) network of thousands of computers and millions of personal computers that are managed independently. Internet easy to use by anyone, even those that have only minimal capabilities. Web is an information delivery using Internet technology. With the web, we can interact in a vast space. Until recently, the website is popular, but its use is required in a design.